Development Of Android-Based Mobile Learning In Financial Accounting Subject Class Xi Accounting At Smk Negeri 10 Surabaya - Rahmat Danang Januar Millenio; Joni Susilowibowo (Institute of Computer Science (IOCS), 2022)
Procurement of this research is intended to explore the development and use of AndroidBased Mobile Learning Media in accounting compartments for class XI accounting in SMK Negri 10 Surabaya. The method of this research is research and development through 4D development methods consisting of four levels: definition, design, development, and dissemination. The equipment used is an extra review sheet, expert verification leaves, and student questionnaire. The final result of the expert verification of the document is 89%. On average, all achieved verification results were 86.46% of the